Ekonomizacja administracji publicznej na tle koncepcji prawnych i społecznych - Kachniarz, Marian (Efficiency of public administration on the background of legal and social cocneptions, 2008)
In the first part of the article its author synthetically talks over the concepts of functioning of administration which are in jurisprudence and social science trends. On that background he discusses new ideas of public services management which are connected with economic science. In conclusions he states that there is a considerable divergence in the approach to the economisation of public administration from the part of jurisprudence and social science.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 165-175